Experimental evidences of quantum confined 2D indirect excitons in single barrier GaAs/AlAs/GaAs heterostructure using photocapacitance at room temperature - Bhunia, Amit; Singh, Mohit Kumar; Galvao Gobato, Y.; Henini, M.; Datta, Shouvik (AIP Publishing, 2018)
We investigated excitonic absorptions in a GaAs/AlAs/GaAs single barrier heterostructure using both photocapacitance and photocurrent spectroscopies at room temperature. Photocapacitance spectra show well defined resonance peaks of indirect excitons formed around the C-AlAs barrier. Unlike DC-photocurrent spectra, frequency dependent photocapacitance spectra interestingly red shift, sharpen up, and then decrease with increasing tunneling at higher biases. Such dissimilarities clearly point out that different exciton dynamics govern these two spectral measurements. We also argue why such quantum confined dipoles of indirect excitons can have thermodynamically finite probabilities to survive even at room temperature. Finally, our observations demonstrate that the photocapacitance technique, which was seldom used to detect excitons in the past, is useful for selective detection and experimental tuning of relatively small numbers ( 1011/cm2) of photo-generated indirect excitons having large effective dipole moments in this type of quasi-two dimensional heterostructures.